Fintech, foreign bank presence and inclusive finance in Africa: Using a quantile regression approach - Khadijah Iddrisu; Joshua Yindenaba Abor; Kannyiri Thadious Banyen (Cogent Economics & Finance, 2022)
Africa is one of the continents with the least inclusive finance. However, with increasing use of mobile phones for financial services or financial technology (Fintech), there are improved opportunities to 'bank the unbanked". Also, there is a significant increase in both the presence of foreign banks and Fintech usage. Hence, we examine the moderating role of foreign bank presence on the Fintech-inclusive finance nexus over the period, 2000-2018. The results show that foreign bank presence does not directly affect inclusive finance, but increases the link between Fintech and inclusive finance. We recommend that African countries need to provide the conducive environment improving the use of Fintech.
Keywords: D31; D63; E44; 015; 043; 330; Africa; Fintech; Foreign bank presence; Inclusive finance; Quantile regression